On the identity of Conisania leuconephra Draudt, 1950 with a description of a new species from Xizang, China (Lepidoptera: Noctuidae: Noctuinae) - Pan, Zhaohui; Zheng, Weilie; Volynkin, Anton V.; Saldaitis, Aidas; Gyulai, Péter; Tóth, Balázs (Zootaxa, 2023)
The identity of Conisania leuconephra (Draudt, 1950) from Yunnan (China) is revised. A new species Conisania sejilaensis sp. nov. is described from Xizang (China). The adults as well as the male and the female genitalia of the new and related species are illustrated.